Nanoarchitecture of Aggregates of Polymethine Dyes - B. I. Shapiro (Тонкие химические технологии)
In recent years, the class of polymethine (cyanine) dyes has attracted increasing attention of researchers in the field of nanotechnology due to the structural features of their chromophore system and their tendency to form polymolecular states – dye aggregates. The processes of the formation of aggregates with new optical and electronic properties in aqueous solutions were studied as exemplified by anionic thyatrimethinecyanine dyes. It was shown that the aggregates are formed by a “block” mechanism from dimers. The nanoarchitecture of the aggregates is determined by the type of the alkyl substituent in the meso position of the polymethine chain of the dye. The C2H5 group promotes the formation of long-wavelength J-aggregates with the “brickwork” packing of molecules. The CH3 group promotes the formation of short-wave H-units with the “stepladder” packing of molecules. The formation of spatial isomers – J- and H-aggregates from cis and trans conformations of dye molecules – was established. Inorganic and organic cations, which stabilize highly organized aggregate structures, have a significant effect on the formation of aggregated forms of anionic dyes. Thus, the work presents the author's ideas about a new scientific direction – the nanoarchitecture of aggregates of polymethine dyes.